Determinan Kepatuhan Wajib Pajak Usaha Mikro Kecil Menengah - Muhammad Ramzi Misykaat; Siti Hartinah (Universitas Muhammadiyah Jakarta, 2022)
This study aims to empirically prove the determinants of taxpayer compliance in Small and Medium Enterprises (MSMEs). This study employs quantitative approach with survey. Primary data was collected using a questionnaire given to SMEs in LTC Glodok Hayam Wuruk. Data were analyzed using SmartPLS. The results of this study indicate that the application of Government Regulation no. 23 of 2018 has a positive and significant impact on taxpayer compliance; Taxpayer awareness has a significant positive effect on Taxpayer compliance; and the firmness of tax sanctions has a positive and significant impact on MSME taxpayer compliance.